The Optimization of Instagram and TikTok Social Media to Help MSMEs Reach Generation Z Customers - Silaban, Indra Marto; Sarif, Muhammad Irfan; Rambe, Rezkinah; Sitepu, Andri Ismail (CV Raskha Media Group, 2025)
Generation Z represents a strategic market segment for Micro, Small, and Medium Enterprises (MSMEs) due to their high digital engagement and purchasing potential. Instagram and TikTok have emerged as dominant social media platforms among Generation Z, emphasizing visual storytelling, short-form video, and interactive content. This study aims to analyze the optimization of Instagram and TikTok as digital marketing tools to help MSMEs effectively reach Generation Z customers. A qualitative descriptive approach was employed through systematic literature review and observational analysis of MSME social media practices. The findings indicate that content creativity, algorithm-oriented features utilization, posting consistency, and audience interaction significantly influence engagement rates and brand awareness among Generation Z users. Furthermore, authentic storytelling and trend-based content enhance purchase intention and customer trust. This research contributes by providing a structured digital marketing framework tailored for MSMEs targeting Generation Z through social media platforms. The results are expected to support MSME digital transformation and sustainable competitiveness in the digital economy